Neighbourhood Cultural Mapping: Lessons Learned from a Pilot Project in Bayshore - Dick, Ben (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2015)
The cultural mapping project in Bayshore was the first of three neighbourhood cultural mapping pilot projects in Ottawa. City-wide cultural mapping in Ottawa had shown Bayshore to have few cultural resources, and socio-economic indicators had shown Bayshore to be a low-income neighbourhood that faced many problems. However, discussions with neighbourhood residents told a different story. Bayshore has many cultural resources, though they are often intangible. Its residents benefit from the neighbourhood’s cultural diversity, as it is one of the most diverse neighbourhoods in the city. Informal networks have been established in Bayshore that provide support to new immigrants, and a wide variety of specialty stores and restaurants have been established nearby to serve this diverse community. The neighbourhood’s diversity may also be supporting the development of a creative cluster nearby. The Bayshore project forced the City’s cultural mapping team to re-think the way culture is defined and categorized.